Students’ Perceptions of English Language Training Organized by Higher Education Language Centers During the Covid 19 Pandemic - Siminto Siminto; Soesanto Soesanto; Joko Sutarto; Eko Handoyo (International Conference on Science, Education, and Technology, 2021)
The language centers at the university provides services in the form of English language training. English training becomes different when it is carried out in the covid 19 pandemic situation. Online training is a solution so that the program planned by this language service unit can run. Through this article, it will be explained about the students’ perceptions of the English language training held by the language center during the Covid 19 pandemic. This article is the feedback for the improvement of the relevant language center. Qualitative by descriptive research design is used in this article. The research subjects were the UNIMUS students from the various departments and faculties. Data collection techniques used are questionnaires and in-depth interviews. The advanced technique used is the observation technique by directly observing the service pattern of the language center and the implementation of English training. These three steps are a form of method/technique triangulation, which is carried out by using the various techniques in data collection, to ensure the data validity. The results of interviews and questionnaires are related to the results of observations. The English language training managed by the UNIMUS Language Center is in line with the university's vision and mission. It is also in line with the theory of training material design and accommodates student needs. However, in its management, there are still many weaknesses and shortcomings. The training materials of the UNIMUS Language Center designed is not yet referring to the curriculum or academic text because it does not yet have an academic text. The design of training materials is based on the needs of service recipients, in this case students. 54% of respondents stated that the material related to the English Proficiency Course they needed for the TOEFL test.